2017
DOI: 10.1116/1.4977075
|View full text |Cite
|
Sign up to set email alerts
|

Label-free detection of hepatitis B virus using solution immersed silicon sensors

Abstract: Highly sensitive solution immersed silicon (SIS) biosensors were developed for detection of hepatitis B virus (HBV) infection in the early stage. The ultrasensitivity for overlayer thickness at the nonreflecting condition for the p-polarized wave is the basis of SIS sensing technology. The change in thickness due to biomolecular interactions and change in refractive index of the surrounding buffer medium were assessed simultaneously using two separate ellipsometric parameters (Ψ and Δ), respectively, from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The signal to noise ratio(SNR) has been calculated from the ratio of change in current after antigen capture to the change in baseline current due to intrinsic fluctuations. It is observed that in most of the recent reports, [41][42][43][44][45] the limit of detection is much higher than 1 fM. Though some of the research reports 1 fM detection limit with higher sensitivities than ERGO sensor in buffer and serum 46,47 their SNRs is lower by at least an order of magnitude than that in the present paper.…”
Section: Resultscontrasting
confidence: 55%
“…The signal to noise ratio(SNR) has been calculated from the ratio of change in current after antigen capture to the change in baseline current due to intrinsic fluctuations. It is observed that in most of the recent reports, [41][42][43][44][45] the limit of detection is much higher than 1 fM. Though some of the research reports 1 fM detection limit with higher sensitivities than ERGO sensor in buffer and serum 46,47 their SNRs is lower by at least an order of magnitude than that in the present paper.…”
Section: Resultscontrasting
confidence: 55%
“…We constructed a LN AFM system (RMS noise ~35 pm) optimized for surface metrology in the semiconductor industry and the uncertainty was estimated by a quantitative method (see Supplementary Table 1 in Supplementary Information) 2628 . The reliability of surface information is now an essential factor because the results of these measurements can be easily distorted depending on the environment and probe conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Applications to a fast and sensitive approach in biosensing can be found in [51]. As an example the label-free detection of hepatitis B virus [52] is reported.…”
Section: Ellipsometrymentioning
confidence: 99%